The concept of transfer to energy effective economy by perfection of energy audit in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In modern conditions of development the energy observation playsthe key role because it is the complex technical-economical inspectionof organization which is being made to receive authentic information onvolume of energy resources used to identify the structure and effectivenessof energy expenses of organization, to detect the possibilities of energysavingand increase of energy effectiveness. By the results of energy observationthe report and energy passport of fuel-energy consumer are beinggenerated. The aim of energy audit is to evaluate the effectiveness offuel-energy usage and work out effective measures to decrease company’sexpenses. In article the steps of energy audit that stimulate its effectiveconducting are improved.